Pénzügyi lokalitás: kiút a válságból? - Szabó, Richárd (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The subprime crises rooted by the globalised financial structure. The worldwide popular stock exhchange investment forms, the financial innovations and the support IT technolgies „help" to rise and collaps the financial markets. If we originated the quick expansion of the crises in the globalised system, then the outcome from the situation, the solution can be based by the localised financial opportunities. In this paper first I try to introduce the local forms of financial institutions. Historycall, its originated from the credit union (CU) , the save and loan association (S&L A) and the shareholders company form. Most local is the CU and the S&L A. Second I try to introduce the „financial localisation ratio" (FLR). This FLR derivated by international (US, UK and German) examples this ratio will be calculated in Hungary. Conclusion: the hungarian financial market and institution system is not enough developed to turn local.